Educação de Jovens e Adultos: uma reflexão sobre a relação de saberes escolares e cotidianidades. - Bezerra., Andrezza Raquel Cirne (2013)
This study aims to analyze the relationship between school knowledge and everydayness in Youth and Adults, considering the everyday as an ontological (Heller, 1970) of people's lives and the understanding that all human activity has on society as the beginning and the end man in his everyday life. In this sense we seek to identify the meaning of school knowledge to learners and young adults in order to understand if / how / the students / school knowledge to relate to their everyday knowledge. Once we understand the everydayness as space / time of incorporation of practices through linkages and meanings constructed by individuals, develop specific knowledge and authentic (Certeau, 1998), we discussed if / how the school performs interaction relationships between school knowledge and everydayness of / the students / girls and adults, trying to recognize if / how the school knowledge promoted changes in the everydayness / the students / participants of this research. Our research subjects were students / the cycles III and IV of the EJA in a public school in the city of João Pessoa, which twenty-seven answered questionnaires, five of these subsequently participated through semistructured interviews. Used as a method of assessing the information content analysis (Bardin, 2006), which, based on a set of techniques that analyzes the communication allows the inference of knowledge related to the context of production, but also to the life situations that are involved with the object of study. We believe that establishing a public school education school for adults and young people, needs to be based on a set theoretical and methodological endorse the role of school socialization of knowledge historically constructed, but to promote a relationship between this knowledge and the knowledge acquired in everydayness subjects, favoring reflections about their realities and encouraging participation as a form of autonomy, which is strengthened by the concept of popular education. In this context, we in the school of the institution that was our field research, an environment conducive to building relationships knowledge, however, it was found that teachers of various degrees (also called subject teachers) working in Youth and Adults find it difficult to establish links between "science" reference (Chervel, 1990) and knowledge of everydayness of his / her students / those, which directs us to the issue of initial and continuing training of these professionals. Thus, we realize that it takes a look at the initial and continuing training of teachers of undergraduate working in adult education as a way to provide the necessary links to work this type of education.